2011
DOI: 10.1308/147870811x566394
|View full text |Cite
|
Sign up to set email alerts
|

Long-term clinical outcome following lower limb arterial angioplasty

Abstract: INTRODUCTION The aim of this study was to determine the clinical outcome of lower limb arterial angioplasty in a busy district general hospital practice. PATIENTS AND METHODS All angioplasties performed from January 1999 to December 2004 were identified and data collected included cardiovascular risk factors, indications for and complications of angioplasty, limb salvage and patient survival rates, and clinically significant re-stenoses. RESULTS 471 interventions were performed in 385 patients (231 men, 154 wo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 27 publications
(25 reference statements)
0
20
0
Order By: Relevance
“…We performed a PTA in our Department of Angiology. Meta-analyses of infra-popliteal PTA show technical success rates of up to 90% [ 13 ][ 14 ]. Leg ulcer healing rates, however, are not improved by primary stent implantation [ 15 ][ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…We performed a PTA in our Department of Angiology. Meta-analyses of infra-popliteal PTA show technical success rates of up to 90% [ 13 ][ 14 ]. Leg ulcer healing rates, however, are not improved by primary stent implantation [ 15 ][ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“… 25 Other studies suggest patient rather than technical factors as the cause of the increased mortality after endovascular treatment. 26 This study demonstrated that there were no differences in the outcomes regarding mortality in diabetic patients with CLI who had concomitant femoropopliteal and infrapopliteal segments atherosclerotic lesions who underwent endovascular revascularization for both segments in the same procedure.…”
Section: Discussionmentioning
confidence: 64%
“…High technical success rates were observed in both groups. In the ET group, 17 studies [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ] reported technical success. An overall success rate of 92.52% (95% CI [89.08%, 94.94%]) was noted ( Figure 2 A).…”
Section: Resultsmentioning
confidence: 99%
“…Symptom improvement was reported in 9 case series [ 8 , 9 , 14 , 15 , 16 , 17 , 18 , 19 , 20 ] for ET procedures, while under FAE treatment, 1 RCT [ 6 ] and 5 case series [ 5 , 23 , 24 , 25 , 26 ] commented on symptom improvement. For ET procedures, the overall rate of symptom improvement was 83.10% (95% CI [73.67%, 89.63%]) ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%